2008
DOI: 10.1007/bf02982661
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and risk for malnutrition among hospitalized elderly people

Abstract: Nutritional risk is associated with depression in aged inpatients. Close case management of the elderly hospitalized patients that include assessment and treatment for both disorders may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 43 publications
7
56
0
4
Order By: Relevance
“…The results maintained in a sub-group analysis on patients with intra-abdominal tumours, whom are at greatest risk for both an impaired NS [7,9] and adverse outcomes after major surgery [12]. The results are comparable to results found in different studies including onco-geriatric patients or elderly hospitalized patients [9,[31][32][33]. Other associated geriatric domain impairments were cognitive and mobility impairments, which were assessed with the MMSE, TUG and risk of falls.…”
Section: Discussionsupporting
confidence: 68%
“…The results maintained in a sub-group analysis on patients with intra-abdominal tumours, whom are at greatest risk for both an impaired NS [7,9] and adverse outcomes after major surgery [12]. The results are comparable to results found in different studies including onco-geriatric patients or elderly hospitalized patients [9,[31][32][33]. Other associated geriatric domain impairments were cognitive and mobility impairments, which were assessed with the MMSE, TUG and risk of falls.…”
Section: Discussionsupporting
confidence: 68%
“…While depression is associated with weight gain in individuals before age 50 years, it leads to weight loss after that age, as was observed in a cohort of US adults (15) . Moreover, studies in hospitalised and communitydwelling elderly showed that depression increased the risk of impaired nutritional status and observed that malnourished patients had higher depression scores (16,17) .The aim of the present study was to assess nutritional status and prevalence of depression and associations between both. Furthermore, we wanted to explore their impact on selfcaring capacity and quality of life in elderly nursing-home residents.…”
mentioning
confidence: 92%
“…Sabbattini et al reported that there is a relation between high PTH levels and sleep disorders in the ESRD population, which might be related to pruritus and bone pain, and those patients who are poor sleepers have lower hemoglobin levels compared with dIScuSSIOn All elderly patients have an increased risk for both malnutrition and depression even if they do not have a chronic illness. For example German et al reported a 28% frequency for depression and a higher rate of malnutrition presence in these depressed patients older than 65 years of age (15). Similarly Feldblum et al reported a malnutrition rate of 18.5% with mini nutritional assessment in a patient group of 259 patients older than 65 years of age (16,17).…”
Section: Resultsmentioning
confidence: 99%